AKIBAT HUKUM TERHADAP PENJUALAN GAS ELPIJI 3 KG DI ATAS HARGA ECERAN TERTINGGI (HET) DI WILAYAH KOTA PEKANBARU - M. Arbi Ubaidillah; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Based on the Decree No. 430 Pekanbaru Mayor of the Year 2015 Adjustments second highest retail price of Liquefied Petroleum Gas Tubes 3 Kg Subsidized in Pekanbaru, that the price per 3 kg LPG cylinder is Rp. 18,000 (eighteen thousand rupiah). But the facts found is still the number 3 kg LPG gas stations that sell above the highest retail price set by the government. From this background, the authors conducted a study titled